Hospital Nurses' Perceptions about Distractions to Patient-Centered Care Delivery. - Kollstedt, Kelly; Fowler, Susan B.; Weissman, Karen (MEDSURG Nursing)
Distractions threaten patient safety and quality of care. The purpose of this study was to explore hospital nurses' perceptions about distractions to the delivery of patient-centered care. Staffing issues, telephone ringing, computer issues, and multitasking were the four highest-rated distractors.